Marine-derived fungus Paramarasmius palmivorus CBMAI 1062 applied to sulphur indigo blue decolorization, degradation and detoxification - Pellizzer, Elisa P. [UNESP]; Giovanella, Patricia [UNESP]; De Faria, Adriano U. [UNESP]; Sette, Lara Durães [UNESP] (FapUNIFESP (SciELO), 2024)
The use of marine microorganisms in the treatment of dyes and textile effluents is promising in view of their tolerance to salinity, a characteristic found in this kind of effluent. In this study, different culture conditions were applied to evaluate the decolorization, degradation, and detoxification of Sulphur Indigo Blue (SIB) by the marine-derived basidiomycete Paramarasmius palmivorus CBMAI 1062. Low salt concentration (SLS) and high salt concentration (SMASHS) media were used. P. palmivorus decolorized 100 % and 91.38 % of SIB after 120 h of growth in the SLS medium and after 168 h of growth in the SMASHS medium, respectively. Laccase activity was detected only in the SLS bioassay. UV-Vis, FT-IR, and GC-MS analyses indicated the occurrence of dye biosorption and biotransformation. In the SLS medium metabolites associated with SIB biotransformation (e.g. aldehyde, alkanes, and phenols) were detected. The toxicity measured by Cucumis sativus decreased from 45.41 % to 24.11 % in the SLS bioassay, while in SMASHS medium there was no change in toxicity. The efficiency for decolorization and detoxification of SIB indicates that microorganisms from the marine environment can be a source for biotechnological application in bioremediation processes carried out under saline conditions, adding value to blue biotechnology.
Keywords: bioremediation; environmental biotechnology; marine mycology; phytotoxicity; textile dyes